Eye tracking in high-performance sports: Evaluation of its application in expert athletes - Hüttermann, S.; Noël, B.; Memmert, D. (International Journal of Computer Science in Sport, 2018)
In the last thirty years, an increasing interest in sport sciences regarding the analysis of expert athletes` gaze behavior has become apparent. This narrative review provides an overview of the use of eye tracking systems in high-performance sports from 1987 to 2016. A systematic search of the PubMed, Scopus, SPORTDiscus, and WebofScience databases was conducted. The search was performed using the keywords eye tracking, eye movement, gaze behavior/patterns, and visual search strategies in combination with high-performance sports, elite athletes, high-class athletes, sport experts, and top-athletes. It yielded a total of 86 studies of which almost half were conducted computer-based or in front of a screen. Most studies dealt with the analysis of gaze behavior during dead ball situations while also focusing on differences between expert athletes and novices. More high-quality intervention studies are essential to determine if there are ideal gaze strategies and, if yes, how it is possible to learn/implement these.